World Markets for Organic Fruits and Vegetables - James J. Ferguson (EDIS)
Pascal Liu and others at the International Trade Center, Food and Agriculture Organization (FAO) of the United Nations, reviewed available literature, conducted surveys and interviewed key players in international organic marketing in 2000 for a report entitled "World Markets for Organic Fruit and Vegetables - Opportunities for Developing Countries in the Production and Export of Organic Horticultural Products."  This fact sheet lists the contents and summarizes the main findings of that report with the intention that this information will aid Florida organic fruit and vegetable growers and others in assessing their export potential for European and Japanese markets. This document is HS977, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2004.